Pengaruh penerapan model discovery learning berbasis media gambar terhadap keterampilan berbicara siswa: Sebuah pendekatan eksperimental - Wahyu Ningsih; Ropita Hutahaean; Risna Wati; Kesia Sry Yanti Br Damanik; Vani Sahat Lestari Sihotang (Universitas Mulawarman, 2026)
This study aimed to determine the effect of the Discovery Learning model assisted by picture media on the speaking skills of elementary school students in picture storytelling activities. A quantitative quasi-experimental design was employed, involving 25 sixth-grade students of SD 175763, Garoga District, in the 2024/2025 academic year, divided into experimental and control groups. The experimental group received instruction using the Discovery Learning model with picture media, while the control group followed conventional learning. Data were collected using a speaking skills rubric encompassing five aspects: fluency, diction, sentence structure, intonation, and coherence of ideas. Paired t-tests at a 0.05 significance level were applied for analysis. Results demonstrated a significant increase in the experimental group across all aspects, with fluency rising from 62 to 89 and coherence of ideas from 57 to 81. The t-test yielded a significance value below 0.05, confirming a statistically significant effect. These findings conclude that the Discovery Learning model integrated with picture media is effective in enhancing elementary school students' speaking skills, particularly in picture storytelling activities.